Honor in foreign policy a history and discussion - Donelan, Michael D. (Palgrave Macmillan history of international thought series, 2007)
This book offers a history of honor in foreign policy, working from both a theoretical and historical perspective. Topics covered include the ideologies of Darwinists, nationalists, and fascists, as well as an account of the greed that goes hand-in-hand with advances in government, offering lessons for the implementation of foreign policy today.